Moisture dynamics modelling in Hyssopi Herba drying process by active ventilation - Kemzūraitė, Aurelija; Raila, Algirdas; Bimbiraitė, Kristina; Kornyšova, Olga; Maruška, Audrius (Journal of Environmental Engineering and Landscape Management, 2009)
Medicinal herbs after their harvesting participate in heat exchange with the environmental, as does each organic and hygroscopic material. Drying helps to conserve the medicinal raw material with the maximal preservation of its quality. The present investigation deals with the influence of the surrounding air factors (temperature and relative humidity) on drying intensity. The study object was aboveground part of hyssop (Hyssopus officinalis L.), i.e. Hyssopi herba was used as medicinal raw material. The aim of the study was to offer a mathematical model of time‐related medicinal herbs moisture dynamics and to show its qualitative agreement with the physical model of diffusion as well as to determine the optimum ventilation intensity of medicinal herbs. Drying of Hyssopi herba using active ventilation was investigated. Ventilation intensity and the parameters of the drying agent influenced the processes of moisture dynamics, the total drying time and the quality of Hyssopi herba. The basic prerequisites of the drying process have been analysed. A mathematical model of moisture dynamics has been proposed and used to show the dependence of theoretical moisture dynamics on ventilation velocity. The obtained experimental values of moisture content dynamics during the drying of Hyssopi herba have been shown to agree with theoretical dependences. Drėgnio kitimo modeliavimas hyssopi herba džiovinant aktyviosios ventiliacijos būdu Santrauka. Vaistiniai augalai, kaip ir kiekviena organinė higroskopinė medžiaga, dalyvauja šilumos mainų procese su aplinka. Džiovinant siekiama konservuoti vaistinius augalus iki reikiamo drėgnio, kiek įmanoma išsaugant jų kokybę. Nagrinėta aplinkos oro veiksnių (temperatūros ir santykinio oro drėgnio) įtaka džiovinimo intensyvumui. Tyrimams naudota antžeminė vaistinio isopo (Hyssopus officinalis L.) dalis, t. y. vaistinė augalinė žaliava – isopų žolė (Hyssopi herba). Tyrimų tikslas – sudaryti drėgmės kitimo per tam tikrą laiką matematinį modelį, taikant gautą difuzijos sprendinį, bei nustatyti optimalų ventiliavimo intensyvumą. Tirtas Hyssopi herba džiovinimo taikant aktyviąją ventiliaciją procesas. Išanalizavus pagrindines džiovinimo sąlygas, sudarytas drėgmės kitimo priklausomybės nuo ventiliavimo intensyvumo, matematinis modelis. Ventiliavimo intensyvumas ir džiovinimo agento parametrai turėjo įtakos drėgmės mainų procesams, džiovinimo trukmei ir vaistinės augalinės žaliavos kokybei. Gauti drėgnio kitimo džiovinant Hyssopi herba rezultatai patvirtino, kad teorinės priklausomybės kokybiškai atitinka tiriamąjį procesą. Reikšminiai žodžiai: Hyssopi herba, drėgnis, difuzija, Fiko dėsnis, eterinis aliejus. Моделирование изменения влажности hyssopi herba в процессе сушки с активной вентиляциeй Резюме. Лекарственные растения, как и всякий органический гигроскопический материал, участвуют в процессе теплообмена с окружающей средой. С помощью сушки требуется консервировать лекарственные растения до нужной влажности, максимально сохраняя их качествo. Исследовалось влияние температуры и относительной влажности окружающего воздуха на интенсивность сушки. Объект исследования – наземная часть лекарственного иссопа (Hyssopus officinalis L.), т.е. лекарственное сырьё Hyssopi herba. Целью исследования было создать математическую модель изменения влажности с течением времени, применяя полученное решение диффузии, и определить оптимальную интенсивность вентиляции. Процесс сушки Hyssopi herba исследовался способом активной вентиляции. Различные параметры интенсивности вентиляции и сушильной среды влияли на процесс влагообмена, продолжительность сушки и качество лекарственного сырья. Произведен качественный анализ основных предпосылок процесса сушки. Предложена математическая модель изменения влажности, и на ее основе получена теоретическая зависимость изменения влажности от интенсивности вентиляции. Полученные результаты подтвердили соответствие между теоретической моделью и экспериментальными данными. Ключевые слова: Hyssopi herba, влажность, диффузия, закон Фика, эфирное масло. First Published Online: 14 Oct 2010